2018
DOI: 10.1016/j.mayocp.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Code Status and End-of-Life Decision Making in Patients With Limited English Proficiency in the Intensive Care Unit

Abstract: There are important differences in end-of-life care and decision making for patients with LEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…There is a growing body of literature that underscores the importance of ethnic, racial, religious, and language barriers in decision-making at the end of life. [1][2][3][4][5][6][7] These factors have been previously studied as predictors and moderators of various aspects of care, including advance care planning, receiving comfort care, and resuscitation preferences. Although low SES has been noted to negatively affect access to care, quality of care, and potentially, health-care outcomes, its role in end-of-life decision-making and care has not been extensively studied, and there is no consensus about its role or importance.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature that underscores the importance of ethnic, racial, religious, and language barriers in decision-making at the end of life. [1][2][3][4][5][6][7] These factors have been previously studied as predictors and moderators of various aspects of care, including advance care planning, receiving comfort care, and resuscitation preferences. Although low SES has been noted to negatively affect access to care, quality of care, and potentially, health-care outcomes, its role in end-of-life decision-making and care has not been extensively studied, and there is no consensus about its role or importance.…”
Section: Introductionmentioning
confidence: 99%
“…Hispanics are less likely than non-Hispanic whites to complete an advanced directive and to have discussions with family members and health care professionals about the type of care they want to receive at the (26). This disparity may be due to several factors including a lack of awareness about advanced care resources (26), language barriers and low health literacy (7,27), disagreement about prognosis and care goals between family members or with clinicians (28), and distrust in the medical system because of negative past experiences (29). The critical role of family in EOL care decision making among Hispanics suggests there is a need for more culturally competent health policies and patient-centered education that facilitate patient and family decision making (5).…”
Section: Discussionmentioning
confidence: 99%
“…A study from 2018 of decedents in one hospital found that it took an average of 19 days longer for patients with limited English proficiency to transition to care focused on comfort compared with English-speaking patients after adjusting for differences in education and insurance status. 34 These challenges make it difficult to forecast how communication interventions might affect care in ICUs serving diverse or disadvantaged populations. Fourth, randomisation levels vary and blinding is nearly impossible in clinical trials of communication interventions.…”
Section: Challenges In the Design And Interpretation Of Icu Communicamentioning
confidence: 99%